2011
DOI: 10.1016/j.cattod.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of CO over gold supported on Zn-modified ceria catalysts

Abstract: A series of Zn-modified ceria solids were prepared by thermal decomposition of the corresponding metal propionates. The formation of segregated ZnO particles on the ceria surface is evidenced for these solids using X-ray diffraction; in addition to this the characterization data may allow discarding the formation of a ZnO-CeO 2 solid solution. On modifying with Zn, the reducibility of the ceria support is enhanced, being the highest reducibility the one obtained for the ZnO-CeO 2 solid having a 1:9 Zn:Ce atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
56
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 45 publications
13
56
1
Order By: Relevance
“…The tetragonalization of the cubic structure by the presence of Ce 3+ species may be confirmed by the broad and small signal centered at 279 cm -1 [51]. The promotion of the oxygen vacancies population by the inclusion of copper species is in good agreement with that widely established by different authors whose demonstrated that the doping of the cerium oxide results in the promotion of oxygen vacancies [14,37,40,52].…”
Section: Physico-chemical Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…The tetragonalization of the cubic structure by the presence of Ce 3+ species may be confirmed by the broad and small signal centered at 279 cm -1 [51]. The promotion of the oxygen vacancies population by the inclusion of copper species is in good agreement with that widely established by different authors whose demonstrated that the doping of the cerium oxide results in the promotion of oxygen vacancies [14,37,40,52].…”
Section: Physico-chemical Characterizationsupporting
confidence: 88%
“…These results are in good agreement with previous reports where ceria-based catalysts loaded with 1 wt. % gold exhibited good performances in the TOX reaction [40,70].…”
Section: Catalytic Performance and Kinetic Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been widely reported that the doping of the CeO 2 structure by the addition of one or more cations with a different nature, allows achieving mixed systems with improved oxygen exchange ability. Many different cations have been successfully used: Zr [11,50], Zn [17,51], Fe [52,53], Co [54], La [55,56], Eu [57], Gd [56], and Sm [58], among others. Taking into consideration the wide range of possible combinations between ceria and different cations, the different synthesis procedures that can be applied to obtain the mixed oxides, and the strict control of the variables required during the synthesis procedures, studies in the near future will be devoted to understanding the structural properties achieved for the obtained solids and to correlating them with their catalytic activity in the CO oxidation reactions, despite the large number of yet published papers in this topic many works.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, presence of Au grows the oxygen vacancies on ZnO [34], also improves the catalysis reactivity. For calcination temperature, lower temperature can lead to smaller Au crystallites, which further lead to higher catalysis reactivity.…”
Section: Sensitivity Analysismentioning
confidence: 99%